Antioxidant Activity and Total Flavonoid Content of Zingiber aromaticum Val. - Sunarto Sunarto; Nur Amalia Choironi; Faridah Laeli Syarifah (Acta Pharmaciae Indonesia : Acta Pharm Indo, 2020)
Increase prevalence of degenerative disease caused by free radicals. Zingiber aromaticum is known to be used as traditional medicine. The purpose of this study was to known antioxidant activity and total flavonoid content of Z. aromaticum from Lembang. The extract was obtained by maceration method using ethanol solvent. Total flavonoid content was carried out using spectrophotometry. The antioxidant activities was carried out by Ferric Reducing Antioxidant Power (FRAP) method. Corellation between total flavonoid content and antioxidant activities using statistic with Pearson’s Correlation method. The results shown that antioxidant activities of Z. aromaticum is weak with total flavonoid content is 9,924 ± 0,544 mg quercetin/ g extract.